Análisis de los sistemas de información contable y su incidencia en la toma de decisiones en los minimarket comercial la economía y emprovit de la parroquia de Pujilí, cantón Pujilí, provincia de Cotopaxi - Tisalema Tasigchana, Blanca Teresa (2017)
This research project was developed at Pujilí canton with the purpose to determine the importance of using the Accounting Information System (AIS) in decisions making. Its main objective was to analyze the incidence of generated information through AIS for decisions made in Comercial la Economía and Emprovit Minimarkets from Pujilí parrish, Pujilí canton, Cotopaxi province, using a scientific question in order to accomplish the set objective. For the investigation development was used a mixed methodology, through the application of surveys and interviews, which allowed to obtain information from administrators and accountants in relation with the use and manage of AIS in studied business. The obtained findings show that AIS are indispensable at the moment to know results of the enterprise at the end of the countable period; in addition, obtained data from them allow to make planning, enterprise control and decisions making with base on the financial and economic information, as well as projecting the future possibilities of the business and its tax information. The research contribution, focuses on informing to the Minimarket of the canton the transcendental part of AIS inside its economic activities, when demonstrating the incidence of the systems in the decision making of the businesses studied. The impact of the project has the perspective of making Minimarket owners aware of the possibility of having an AIS to better manage their accounting.